KNOWLEDGE MANAGEMENT SYSTEMS DESIGN innovation and strategy. - Husain, Shabahat; Ermine, Jean-Louis (ROUTLEDGE, 2025)
"Knowledge Capital, which ensures the sustainability, competitiveness, and stability of an organization, can be regenerated in a value-added form, made available for creating quality products and services through the application of innovative Knowledge Management techniques. This includes setting up and applying ISO-compliant Knowledge Management Systems (KMS) across various domains. The book includes practical case studies providing a thorough analysis of the necessary procedures and technologies for KMS development. It also highlights innovative frameworks like the Virtuous KM Cycle, MASK techniques, Daisy Model, and the Husain-Ermine AI-KM Model. Covering nearly all facets of KM, the book details the evolution and provides a clear depiction of fundamental theories, leading to the latest trends in integrating Artificial Intelligence with KM practices. Also discusses the challenges of measuring the effectiveness of KM techniques and the value they add to an organization, which helps make the adoption of KM more likely to succeed and be sustainable. As such, this book serves as an essential resource for students and researchers in Knowledge Management, and for managers, academicians, and professionals in both public and private sectors"-- Provided by publisher.
Keywords: Knowledge management.; elektronické knihy; electronic books